The Effect Of Using Mobile Legend Game Toward The Learning Vocabulary Mastery At Eight Grade Of Smp Muhammadiyah 17 Desa Pon - Dhea Murti Ananda, Ahmad Laut Hasibuan (CV. PUSDIKRA MITRA JAYA, 2023)
The objective of the research was to find out whether there is a significant effect of using mobile legend game media on student achievement in vocabulary mastery. This type of research is quantitative research and was conducted using two classes as research samples, namely class VIII-A as an experimental class consisting of 31 students and class VIII-C as a control class consisting of 31 students. In technique of collecting data, the researcher conducted pre-test, treatment and post-test by giving an understanding test of vocabulary consisting of 20 test, namely 10 true or false questions and 10 matching questions. The result of this research show that there was a significant effect of using mobile legend game media on students' vocabulary mastery. It can be seen after calculating and analyzing the t-table df 60 (n+n-2 = 31+31-2) at t-critical 0.05, it is obtained 1.67. If compared the value of to and tt, so it shows that the value of t-observed is bigger than the value of t-table or 2,56> 1,67. It means that class VIII students of SMP Muhammadiyah 17 Desa Pon apply mobile legend game media in vocabulary learning higher than without mobile legend game media. After testing the hypothesis of the research, it was found that the hypothesis was accepted.